Retrofitting of ex-vessel core catchers into operating nuclear power plants at the example of a Mark-I BWR. (October 2020) - Fischer, Manfred; Keim, Torsten
Highlights: Core melt stabilization concepts are assessed for retrofitting in Gen-II plants. Design conditions in existing plants are analyzed and requirements formulated. Exemplary analysis of melt stabilization in a Mark-I BWR containment. Abstract: The safety of operating nuclear power plants (NPPs) can be improved either by strengthening the preventive and/or the mitigative path. Though, preventing the accident in the first place is of highest priority, it is evident that, at some point, further improvements in preventive features will no longer lead to a proportional increase in safety, nor can they completely eliminate all possible sequences leading to core melting. Mitigation features can limit and contain the otherwise high negative consequences of a severe accident, by preserving the integrity of the containment under severe accident conditions. One of the relevant containment failure modes is basemat melt-through. Its potentially high relevance has been demonstrated by the Fukushima-Daiichi accidents in which the uncontained interaction of the core melt with the basemat concrete led to long-term activity releases, high costs for containing them, and complicated post-accident fuel removal. While new-build Gen-III NPPs typically prevent molten core-concrete interaction (MCCI) by implementing dedicated measures for core melt stabilization (CMS), no such provisions exist in operating Gen-II plants and therefore would have to be retrofitted. Though retrofitting can result in high related efforts and costs, it may nevertheless be an option in countries where corresponding safety improvements are recommended or even required to either regain the operational license or extend the plant's lifetime. In this context, Framatome investigated various CMS concepts with respect to their suitability for Gen-II retrofitting, building on the experience gained during the conceptual development of the EPR. One general finding of this exercise was that the chosen best-fit solution always depends on the specific constraints of the plant under consideration, as well as on other aspects, like the spectrum of conditions and assumptions to be covered and the functional requirements to be fulfilled. Last but not least, the solutions must remain simple enough so that efforts for installation and service and the related cost and time constraints stay in an acceptable relation to the achievable safety gain. The paper first provides an overview of the applicable technical solutions, including their specific benefits and disadvantages, then lists the typical functional requirements and limitations and shows which ex-vessel solutions have the highest potential and are currently considered or used for retrofitting. Finally the results of a screening of available melt stabilization solutions for an exemplary Mark-I boiling water reactor (BWR) containment are given.